2023
DOI: 10.1002/rmv.2424
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and vascular biomarkers in post‐COVID‐19 syndrome: A systematic review and meta‐analysis of over 20 biomarkers

Abstract: Severe acute respiratory syndrome coronavirus 2 may inflict a post-viral condition known as post-COVID-19 syndrome (PCS) or long-COVID. Studies measuring levels of inflammatory and vascular biomarkers in blood, serum, or plasma of COVID-19 survivors with PCS versus non-PCS controls have produced mixed findings. Our review sought to meta-analyse those studies. A systematic literature search was performed across five databases until 25 June 2022, with an updated search on 1 November 2022. Data analyses were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 106 publications
(142 reference statements)
5
40
1
1
Order By: Relevance
“…Sixth, the use of multiple time points run the risk of introducing precision error in our pooled estimates. We identified two systematic reviews that reported on 113 107 and 18, 108 potential biomarkers of long COVID from 28 to 23 included studies with last searches in August and November 2022 respectively 107,108 . Lai et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixth, the use of multiple time points run the risk of introducing precision error in our pooled estimates. We identified two systematic reviews that reported on 113 107 and 18, 108 potential biomarkers of long COVID from 28 to 23 included studies with last searches in August and November 2022 respectively 107,108 . Lai et al.…”
Section: Discussionmentioning
confidence: 99%
“…107 In contrast, Yong et al did a pooled analysis and reported a significantly higher levels of CRP (10 studies), D-dimer (11 studies), LDH (8 studies) and leucocytes (7 studies) in PASC. 108 However, neither of them reported on LDH association with specific PASC domains, most probably due to limited LDH data.…”
Section: Study Limitationsmentioning
confidence: 99%
“…3,4,[10][11][12][13] The aetiology of long COVID remains uncertain, though several underlying pathophysiological mechanisms, such as cellular damage, inflammatory cytokines and a hypercoagulable state, are thought to contribute to long COVID inception and trajectory. 7,[14][15][16][17] Given the complexity of the condition, a diverse range of potential predictors warrant consideration. Older age, female sex, pre-existing conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,15,[18][19][20] Additionally, a number of biomarkers have been investigated but currently, there is no consensus as to whether any characterize long COVID. 14,16,17 Investigation of potential serological markers of long COVID, accounting for clinical covariates, may yield pathophysiological insights. To date, several observational studies have compared humoral response between groups with and without persistent symptoms, albeit with highly mixed findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation